1968
DOI: 10.3133/pp570
|View full text |Cite
|
Sign up to set email alerts
|

Geology and ore deposits of the Iron River-Crystal Falls district, Iron County, Michigan

Abstract: Western sector.________________________________ Central sector._________________________________ Eastern sector._________________________________ Bedrock geology.___________________________________ Nomenclature of Precambrian units.______________ General outline of stratigraphy.__________________ Stratigraphy. __^____-__________________________ Greenstone in the Brule River area ___________ Saunders Formation ______________________ Description. ___________________________ Thickness and relations to adjacent fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 18 publications
(33 reference statements)
2
27
0
1
Order By: Relevance
“…In the 36 Figure 2B. Simplified geologic map of study area (after Gair and Weir, 1956;Bayley, 1959;James and others, 1966;Weir, 1967;James and others, 1968;Dutton, 1971). …”
Section: Regional Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…In the 36 Figure 2B. Simplified geologic map of study area (after Gair and Weir, 1956;Bayley, 1959;James and others, 1966;Weir, 1967;James and others, 1968;Dutton, 1971). …”
Section: Regional Geologymentioning
confidence: 99%
“…Unlike the aforementioned groups, the Paint River Group occurs exclusively in the Crystal Falls and Florence areas and nowhere else in the Lake Superior region (what will later be called the Crystal Falls terrane and Florence-Niagara terrane). James and others (1968) argued that the Paint River Group is stratigraphically the youngest early Proterozoic succession in the Lake Superior region. Cambray (1978) suggested that the Paint River Group strata and underlying pillow basalts are the equivalent of the Menominee Group.…”
Section: Regional Geologymentioning
confidence: 99%
“…1880 Ma iron formations of the Animikie basin and were likely deposited in deeperwater, below fair-weather and, probably, storm wave base settings. They are present in the: (1) Marquette Iron Range, Michigan (~60-m-thick Bijiki Iron-Formation Member of the Michigamme Slate containing siderite, chert, iron oxides, and silicates; Ojakangas, 1994;Ojakangas et al, 2001;Cannon et al, 2010), (2) Iron River-Crystal Falls Iron Ranges (~15-m-thick chert-siderite slate of the Stambaugh Formation; James et al, 1968), (3) Gogebic Iron Range, Wisconsin (~47-m-thick iron formation of the Tyler Formation consisting of chert and siderite; Schmidt, 1980;Cannon et al, 2008), and (4) Mesabi Iron Range, Minnesota (~27-m-thick chertsiderite iron formation in the lower part of the Virginia Formation; Lucente and Morey, 1983). Deposition of these iron formations might be genetically related to submarine mafic volcanism in the Animikie basin based on spatial association with, for example, the Badwater Greenstone, but this relationship has not been documented in detail.…”
Section: Ca 193 To 185 Ga Iron Formations Coeval With Large Vms Dementioning
confidence: 99%
“…The southern more mobile segments have thicker sequences of sediments interbedded with volcanics (Sims et al 1980). The thickness of the Negaunee Iron Formation is 7500 m in the south and thins northward to 2000 m (James et al 1968). …”
Section: Introductionmentioning
confidence: 96%